2004
DOI: 10.1017/s1355617704106012
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of global outcome with acute neuropsychological testing following closed-head injury

Abstract: Delaying assessment until emergence from post-traumatic amnesia increases completion rates, but this practice causes variable time delays from the date of injury to testing, which can complicate the interpretation of research findings. In the current study, the performance of 105 head injury survivors on simple tests of language comprehension and attention was used to predict global outcome. It was hypothesized that 1 month performance on these measures would aid in the prediction of Disability Rating Scale (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…Kalmar et al [29] found that testing was feasible early after moderate-to-severe TBI, regardless of PTA status. Pastorek et al [30] examined language and attention as part of neuropsychological testing during PTA and concluded that testability itself during PTA was indicative of outcome. These studies indicate that assessment of various cognitive functions may be feasible and productive during PTA.…”
Section: Cognitive-communication and Ptamentioning
confidence: 99%
See 1 more Smart Citation
“…Kalmar et al [29] found that testing was feasible early after moderate-to-severe TBI, regardless of PTA status. Pastorek et al [30] examined language and attention as part of neuropsychological testing during PTA and concluded that testability itself during PTA was indicative of outcome. These studies indicate that assessment of various cognitive functions may be feasible and productive during PTA.…”
Section: Cognitive-communication and Ptamentioning
confidence: 99%
“…This difficulty may be compounded by the absence of supporting speech pathology literature on the impact of PTA on communication or research on communication recovery early after TBI. Early prognostic factors relating to communication are still largely unknown, although recent research into the predictive value of neuropsychological testing during and shortly after PTA has indicated that there are aspects of clinically observable behaviour that may provide valuable information about outcome [26,30,35].…”
Section: Monitoring and Predictionmentioning
confidence: 99%
“…This variability has led to a focus on identifying factors predicting or indicating functional outcome. Studies conducted up to 3 years after injury have found that outcome may be influenced by injury severity, as measured by Glasgow Coma Scale (GCS) scores or duration of posttraumatic amnesia (PTA), demographic factors, including age, gender, and preinjury education and employment, as well as postinjury cognitive and social factors (Brown et al, 2005;Cattelani et al, 2002;Dikmen et al, 1995b;Fleming et al, 1999;Godfrey et al, 1993;Gollaher et al, 1998;Ip et al, 1995;Levin et al, 1990;Pastorek et al, 2004;Ponsford et al, 1995;Rothweiler et al, 1998;Van der Naalt et al, 1999;Van Zomeren & Van den Burg, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The research literature includes several studies that have explored how factors such as demographic and pre-morbid characteristics of the individual (age, presence of prior neurological conditions, educational level, employment level or history of drug/alcohol abuse), severity of injury, type and location of lesions, early cognitive functioning or posttraumatic amnesia (PTA) influence cognitive outcome and functional and employment status in the first year post injury [18][19][20][21][22][23]. Less information is available, however, about the relationship between such variables and impairments in language and communication.…”
Section: Introductionmentioning
confidence: 99%